Universal screening for hypothyroidism in pregnancy: is it necessary? - V., Meena Priyadharshini; Panicker, Seetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Thyroid diseases are one of the commonest endocrine disorders affecting women of reproductive age group, and hence constitute one important disorders complicating pregnancy. The objective of this study was to determine the importance of universal screening for hypothyroidism in pregnancy at the first antenatal visit and to formulate whether this routine screening is mandatory in our country. Methods: This retrospective study was conducted in the year 2018 at PSG IMSR Hospital for all pregnant women who attended the first antenatal visit between Jan 2012 to Dec 2012 after obtaining ethical clearance. Pregnant women who were already taking treatment for hypothyroidism, diabetes mellitus, hypertension and those pregnant women who lost their follow up were excluded from the study. Results: The incidence of subclinical hypothyroidism among antenatal women were 7.06%. In our study the maternal complications like anemia 12 (8%), preeclampsia 26 (17.3%), gestational diabetes 25 (16.7%), fetal growth restriction 8 (5.3%), Oligohydramnios 13 (8.7%), pre mature rupture of membranes 25 (16.7%), placental abruption in 2 (1.33%), APLA syndrome 2 (1.33%), low birth weight 26 (17.3%) were observed. Conclusions: Universal screening for hypothyroidism is recommended for all antenatal women especially in iodine depleted country like India.